Peran Keluarga Dalam Menjaga Kesehatan Mental Anak Dalam Perspektif Zakiah Daradjat - Zanatul Faizah; Iva inayatul Ilahiyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The family is someone who is responsible for the social development of children. Because in essence, the family is the first and main forum for the growth and development of children. If the atmosphere in the family is good and pleasant, then the child will grow well, if not, the child's growth will certainly be hampered. Apart from being the first forum, the most important role in the family is to meet the child's needs, both physical and psychological. Meanwhile, mental health is a condition where an individual is free from all forms of symptoms of mental disorders. Mentally healthy individuals can function normally in living their lives, especially when adapting to face the problems that will be experienced throughout one's life. Meanwhile, children are a trust and a gift from God, in fact children are considered the most valuable assets compared to other assets.